Trends in Therapeutic Communication Skills Research in Nursing Education Journals throughout Indonesia: from Research Design to Analysis - Vernando Yanry Lameky (Aloha International Journal of Health Advancement (AIJHA), 2022)
Therapeutic communication skills are one of the goals to be obtained in 21st century education. This study uses content analysis on a collection of articles that have been published in nursing education journals throughout Indonesia from 2006 to 2021, with emphasis on research on therapeutic communication skills. This research shows that in the last three years, the number of publications that prioritize therapeutic communication skills has not progressed. In the collection of publications, the most types of research designed are qualitative, the research design is descriptive research design to correlation research, the largest research subject is patients and the topic of material is family with the most treatment, namely the relationship with the findings of this study, several recommendations have been proposed for research. future that supports therapeutic communication skills as a primary focus. Some of these recommendations include increasing the diversity of types of research and choosing more appropriate data analysis techniques. Keywords: Nursing education; Skills; Therapeutic communication